Public and Tourist Perceptions of Marine Tourism Development of Anambas Islands Regency - Pristiwasa, I Wayan Thariqy Kawakibi; Br.Ht.Gaol, Nurfratna Sari (Ridwan Institute, 2024)
The Anambas Islands Regency, situated within the Riau Islands province with its center in Tarempa, boasts a captivating array of marine tourism attractions, including pristine white sandy beaches, crystalline waters, and breathtaking natural scenery. Beyond surface beauty, the underwater marine ecosystem harbours significant potential for development. Notable sites include Penjalin Island, strategically positioned and directly accessible from Singapore, Malaysia, and Vietnam; Pulau Bawah, renowned for its three stunning lagoons and rich mangrove exploration; Durai Island, home to unique habitats including leatherback turtle nesting grounds; the picturesque Green Rafting Beach with its enchanting coral landscapes; Temawan Island, offering both beachfront leisure and diverse underwater ecosystems; and Tanjung Momong, boasting captivating coral reefs. This study investigates public and tourist perceptions regarding the development of these marine attractions in the Anambas Islands. Utilizing quantitative methods, data was collected via questionnaires from 250 respondents selected using the Slovin formula. Descriptive analysis employing SEM-AMOS revealed that perceptions of marine tourism development positively impact regional income, economy, and community welfare. This research underscores the significance of leveraging Anambas' marine resources for sustainable economic growth and societal well-being.